Building Customer Loyalty of Indihome Bireuen: The Role of Product Quality, Marketing Strategy, and Brand Image - Syahril Ramadhan; Muhammad Salim; Sinta Amelia; Nurmasyitah; Rahmatul Ulia (Journal Informatic, Education and Management (JIEM), 2026)
This study is entitled “Building Customer Loyalty of Indihome Bireuen: The Role of Product Quality, Marketing Strategy, and Brand Image.” The purpose of this research is to analyze the influence of product quality, marketing strategy, and brand image on Indihome customer loyalty in Bireuen Regency. The study was conducted in Kota Juang District, precisely in Pulo Ara Geudong Teungeh Village, Aceh Province, involving 108 Indihome customers as respondents. The findings indicate that product quality and brand image have a positive and significant effect on customer loyalty, where service attributes such as internet speed, network stability, and Indihome’s reputation as part of Telkom Indonesia play a crucial role in maintaining customer commitment. Meanwhile, marketing strategy does not have a significant partial effect; however, when combined, the three variables (product quality, marketing strategy, and brand image) exert a significant influence on customer loyalty, with a coefficient of determination of 78.4%. These results imply that managing product quality and strengthening brand image should be prioritized, alongside refining marketing strategies to better align with the characteristics of the local community. This research is expected to provide valuable insights for Indihome’s management in formulating strategies to retain customer loyalty and to serve as a reference for future studies in similar contexts.